Experimental Rock Deformation - The Brittle Field - Paterson, M.S; Wong, Teng-fong (Springer Berlin Heidelberg : Imprint: Springer, 2005)
This monograph deals with the part of the field of experimental rock deformation that is dominated by the phenomena of brittle fracture on one scale or another. Thus a distinction has been drawn between the fields of brittle and ductile behaviour in rock, corresponding more or less to a distinction between the phenomena of fracture and flow. The last chapter deals with the transition between the two fields. In this new edition an attempt has been made to take into account new developments of the last two and a half decades. To assist in this project, the original author greatly appre- ates being joined by the second author. The scope of the monograph is limited to the mechanical properties of rock viewed as a material on the laboratory scale. Thus, the topic and approach is of a "materials science" kind rather than of a "structures" kind. We are dealing with only one part of the wider field of rock mechanics, a field which also includes structural or boundary value problems, for example, those of the stability of slopes, the collapse of mine openings, earthquakes, the folding of stratified rock, and the convective motion of the Earth's mantle. One topic thus excluded is the role of jointing, which it is commonly necessary to take into account in applications in engineering and mining, and pr- ably often in geology too. Shock phenomena have also not been covered.